2010
DOI: 10.1007/s10389-010-0317-y
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of health risk behaviours and their interrelationships among young people from two counties of Romania

Abstract: AimThe first goal of this study was to assess the prevalence of different health risk behaviours among Romanian young people. Next, the interrelationship between different health risk behaviours as well as age and gender differences with respect to health risk behaviours were examined.Subjects and methodsSelf-administered questionnaires were completed by a sample of 1,598 junior high school students, senior high school students and university students from urban and rural areas of two counties of Romania.Resul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2010
2010
2025
2025

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 30 publications
0
5
0
Order By: Relevance
“…One explanation for this international public health problem is that adolescents demonstrate a heightened propensity, or inherent inclination, to take risks (Steinberg 2008). Findings from cross-sectional studies of risk behavior conducted in various parts of the world suggest that adolescents do generally take more risks than adults (Eisner 2002; Donato et al 1995; Lotrean et al 2010; Takakura et al 2001). This seems to be particularly true with respect to antisocial risk behaviors, such as theft (Eisner 2002), whereas young adults demonstrate the highest levels of risk taking with respect to various health risks, such as binge drinking (Willoughby et al 2013).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…One explanation for this international public health problem is that adolescents demonstrate a heightened propensity, or inherent inclination, to take risks (Steinberg 2008). Findings from cross-sectional studies of risk behavior conducted in various parts of the world suggest that adolescents do generally take more risks than adults (Eisner 2002; Donato et al 1995; Lotrean et al 2010; Takakura et al 2001). This seems to be particularly true with respect to antisocial risk behaviors, such as theft (Eisner 2002), whereas young adults demonstrate the highest levels of risk taking with respect to various health risks, such as binge drinking (Willoughby et al 2013).…”
Section: Discussionmentioning
confidence: 99%
“…A study of alcohol use among Italian youth demonstrated greater drinking among young adults ages 18–19 compared to teens ages 14–15 (Donato et al 1995). Furthermore, a study of Romanian youth ages 11–15, 15–19, and 19–25 (Lotrean et al 2010) indicated that fighting, vandalism, smoking, and intoxication was greater in each successive age group (although for some risks, such as illicit drug use, teens ages 15–19 did not differ from young adults). Consistent with epidemiological reports (WHO 2014), risk behavior in each of these studies was greater among males compared to females in all age groups.…”
Section: Introductionmentioning
confidence: 99%
“…The study used an anonymous questionnaire developed for this study based on data from the literature and on previous questionnaires developed and tested in several studies from Romania [2,15,16,24]. It included several sections investigating health risk behaviors among participating students.…”
Section: Instrument For Data Collectionmentioning
confidence: 99%
“…Several studies from all over the world, including Romania, have proved that cigarette smoking is associated with several risk behaviors such as alcohol abuse and illicit drug use among different groups of young people, while the synergistic effects and augmented risks associated with concurrent use of nicotine and alcohol or other illicit drugs have been well established [15,16]. Recently, some studies, especially from North America, have focused on the relationships between e-cigarette use and risk behaviors, but few studies have been performed in Europe, and no data are available from Romania [3,[17][18][19][20][21][22][23].…”
Section: Introductionmentioning
confidence: 99%
“…In contrast, health promotion programs for adolescents should address them directly, but must be sensitive to developmental changes during this rebellious and experimental age (Lotrean et al 2010). For accurate identification of factors of health risk behavior and of effective prevention, intervention programs should consider interrelationships between different health risk behaviors in young people.…”
mentioning
confidence: 99%